Prenatal care performed by a resident in nursing obstetrics in the basic health network (Research, Society and Development, 2022)
Pregnancy is a physiological phenomenon of singular importance in the life of women and their families. Quality prenatal care is an important factor in reducing maternal mortality, and improves the quality of childbirth for both the child and the pregnant woman, demonstrating maternal and infant benefits. Objective: to report and experience about prenatal care performed by a resident in obstetrical nursing in the Basic Health Network. This is a descriptive, qualitative study of the experience report type, based on the experience of a resident in obstetric nursing. Prenatal, postpartum and childcare follow-up is one of the service segments, from conception to early childhood, which demonstrates that singular and integral work makes a difference in the lives of these clients and families. Nurses are trained to work in low-risk prenatal care, being able to provide quality care, as they have care practice and knowledge in identifying risk factors.